Psychiatric illnesses among Dalit Nepalese population (Nepal Journal of Epidemiology, 2014)
Background   Nepalese population includes a wide variety of ethnic groups namely, the Brahmin, Chettri, Dalit, Gurung, Newar, Puns, Magar Dalits population in Nepal are a traditionally victimised, underprivileged community who have been obliged to lag at the base of the public constitution in Nepal.  Dalits Nepalese has poor income, education and other human development indicators. They are often landless and much poorer than the dominant caste population like the Brahmins, chetris, newars. The main objective of the study was to find out the commonest psychiatric disorder found in the poor Dalit Nepalese population in western development region of Nepal for which hospitalization is required. Method The study was a cross sectional study carried out between 1st October- 31st March 2010 at Psychiatric ward in Manipal Teaching hospital. The diagnosis of the disease was based on ICD-10 (Tenth revision) Classification of mental and behavioral disorders, Diagnostic Criteria for Research.. Results Among all the psychiatric diseases Schizophrenia, Schizotypal and Delusion Disorders 30.6%  was the commonest disease seen in the Dalit Population followed by Mental and behavioral disorder due to Psychoactive Substance abuse 20.8%. Psychiatric diseases were more common in male patients 52.8%. 87.5% of the cases were